Atenção primária como cenário de prática na escola médica - Alice Werneck Massote (2011)
The inclusion of medical students in primary health care services (APS) in order to promote a learning linked to real needs of the population's health has been the subject of studies in medical education for several years, both in Brazil and abroad. The Medical School of the Federal University of Minas Gerais (FM/UFMG) first inserted its students in Primary Care scenarios in 1975 and now, it seeks a broadening of its insertion programs. This research aimed to investigate the FM/UFMG 8th semester students perception of the activities performed at the primary health care facilities (CS), following the reinsertion of the FM/UFMG institution in primary health care. The specific objectives were contextualize the inclusion of FM/UFMG in APS from the use of CS as a teaching scenario; identify and describe the activities realized by 8th semester students at the health centers, taking as a reference the Unified Health Systems (SUS) proposals for the APS; search the 8th semester students opinion on activities performed in CS taking as a reference the Unified Health Systems (SUS) proposals for the APS regarding the following aspects: conducting extra-unit activities, participation in unit activities and integration of students with the team. This is a case study of qualitative approach, which sought to articulate the methods and techniques to investigate the object of interest. In this study we selected three CS of the Municipality of Belo Horizonte (PBH) which serves as a practical scenario of FM/UFMG for nearly 30 years. Data collection was performed by means of documentary analysis, focus groups and observation, the latter as a complementary technique. The studied population was composed by the students of 8th semester of medical school entered in the three selected CS. Two focus groups were conducted with six students each. There were also realized 16 hours of observation in each CS, totaling 48 hours, recorded in a diary. For the data treatment it was used the Content Analysis. The documental analysis did a brief review of literature on medical education from the institutionalization of so-called scientific medicine and the resulting movements, which criticized this model, contextualizing them also in Brazil. Moreover, were examined the proposed changes in Brazilian medical education in light of government policies such as the National Curriculum Guide for the Medical School, incentive policies and their consequences. In this context, it was proceeded to a historical review of the integration of FM/UFMG students in CS, presenting the main aspects of the curriculum reform of 1975 and the process of curriculum change in course. The results of focus groups and observations showed, by students, positive perceptions of inclusion in the CS and the recognition by them of the importance of this stage in the medical training process, and contribute to build a new look on health-disease process, enabling the establishment of links and a comprehensive care to population health. Although the clinical consultation still constitutes the main activity carried out by CS, is also valued other activities under this scenario. As a conclusion, this work reinforces the importance of the insertion of medical students into the APS during their formation process.